Legal Status of the Honorary Consul - Dela, Mirosław (University of Wroclaw. Faculty of Law, Administration & Economics, 2014)
The author addresses the issue of the functioning of honorary consuls, focusing on such aspects as the procedure for their appointment, their tasks, rights and duties towards the authorities of the sending State and the receiving State, principles of the functioning of the honorary consular offices they lead, completing the exercise of consular functions. These issues are analysed in two respects – first, regulations on the activities of Polish honorary consuls in foreign countries, then regulations on the activities of honorary consuls of foreign countries in Poland. The article contains an analysis of international law (Vienna Convention on Consular Relations), and two Polish statutes (the Act on the functions of consuls of the Republic of Poland and Regulation of the Minister of Foreign Affairs on honorary consuls of the Republic of Poland). In addition, fragments of an unpublished guide of the Ministry of Foreign Affairs of the Republic of Poland are analysed, addressed to foreign diplomatic missions accredited in Warsaw.
Keywords: honorary consuls; international law